The Moderating Role of Gender in the Relationship among Organizational Justice, Commitment, Job Satisfaction and Organizational Citizenship Behaviors of Secondary School Teachers - Riffat-un-Nisa Awan, Ghazanfar Ali, Sobia Anjum (PJE, 2023)
This study intends to search the structural relations among organizational justice, job satisfaction, supervisor support, organizational commitment, and organizational citizenship behaviors (OCBs) of a sample of 500 secondary school teachers (SSTs) of district Sargodha using a survey research design. The analyses revealed that all demographic variables had insignificant effects on most of the organizational citizenship behaviors of SSTs while only gender had significant effects as a moderator variable. Regression analysis revealed affective commitment and operational justice were significantly correlated to all dimensions of citizenship behaviors, whereas only sportsmanship behavior of teachers was related to normative commitment and interactional justice. Teachers’ compliance behavior and civic virtue were correlated with continuance commitment. Gender turned out to be a significant moderator between the relationships of the pairs of variables such as; continuance commitment and civic virtue, affective commitment and compliance, interactional justice and helping, operational justice and civic virtue, job satisfaction and sportsmanship, continuance commitment and sportsmanship